Pengaruh Media Pembelajaran Terhadap Kemampuan Mengenal Angka Anak Usia 5-6 Tahun di Raudhatul Athfal - Helen Sabera Adib; Fransiska Eva Gelista Gelista (ABNA : Journal of Islamic Early Childhood Education, 2020)
The problem in this study is that the ability to recognize numbers in children is still lacking. The purpose of this study was: to determine the effect of the ability to recognize intermediate numbers using audio-visual learning media and picture card media. This research is an experimental method carried out at RA GUPPI 1 Kalijambe, Sragen from February to September 2020. The sampling technique uses random sampling with cluster sampling. Population of 70 children and sample of 50 children. Methods of data collection using tests with analysis of the mean, median, mode and standard deviation. The prerequisite test uses the normality test, homogeneity test and hypothesis testing. The results showed that the value of u count was 325, while the value of u table at the 5% significance level was 211 so that t> t table was 325> 211. So that the proposed alternative hypothesis was accepted. This shows that there is an effect of differences in the ability to recognize children's numbers between those using audio-visual learning media and picture card learning media.